IMPROVEMENT OF THE PRODUCTION TECHNOLOGY OF COMPLEX KNITTED SUIT FABRICS WITH MIXED COMPOSITION (American Journal of Technology and Applied Sciences, 2025)
This article is intended for the production of currently relevant mixed-composition suit fabrics and describes the wide application of this technology to manufacturing enterprises throughout our Republic and the possibility of increasing economic efficiency and producing quality products.